An ARX-based method for the vibration control of flexible beams manipulated by industrial robots. (August 2018) - Kapsalas, C.N.; Sakellariou, J.S.; Koustoumpardis, P.N.; Aspragathos, N.A.
Highlights: A method for the vibration control of flexible beams handled by robots is introduced. The robot-beam system dynamics is represented by stochastic, data-based, ARX models. A controller is developed based entirely on the ARX model and not the real system. A single pair of signals obtained from the robot are used for the controller's design. The controller's design is fast and its implementation simple for any industrial robot. Abstract: The vibration control problem of flexible objects manipulated by industrial robots under normal production conditions is investigated. This is an important problem as the quick and precise manipulation of such objects may reduce the production lead time and thus its cost. The problem is in the present study tackled for flexible beams via a novel method which overcomes various practical difficulties and can be easily applied in industrial environments with the least human intervention. The method is based on: (i) AutoRegressive with eXogenous (ARX) input stochastic modeling of the robot-beam system using exclusively experimental data, (ii) the design of an appropriate control system consisting of a typical feedforward PID-type controller and a feedback that enables the attenuation of the force at the robot's wrist and thus the suppression of the vibration at the beam's free-end and, (iii) a synthetic environment within which the performance of the control system may be tested under realistic operating conditions through simulation before its final implementation in the robot. The effectiveness of the method is experimentally assessed through the vibration control of a flexible metallic beam that is manipulated by an industrial robot for its insertion into a slot, testing additionally the control system's performance under various operating conditions for which it is not designed to deal with.